Unveiling the Burden of Interactions Among Clinical Risk Factors for 1-Year Mortality in Hospitalized Older Patients - Lattanzio, Fabrizia; Corigliano, Valentina; Soraci, Luca; Fumagalli, Alessia; Onder, Graziano; Volpato, Stefano; Cherubini, Antonio; Ruggiero, Carmelinda; Cozza, Annalisa; Guarasci, Francesco; Corsonello, Andrea (Frontiers in Medicine, 2021)
Abstract Background. Hospitalized older patients are particularly exposed to adverse health outcomes. Objective. In this study, we aimed at investigating the prognostic interactions between disability in Basic Activities of Daily Living (BADL), cognitive impairment, low handgrip strength, anticholinergic cognitive burden (ACB), and depression on 1-year mortality. Setting and subjects. Our series consisted of 503 older patients discharged from acute care hospitals. Methods. Disability in at least 1 BADL, ACB, depression, cognitive impairment, and low hand grip strength were considered in the analysis. 1-year mortality was investigated by Cox regression analysis and prognostic interactions among study variables were assessed by survival tree analysis. Results. BADL disability, ACB, cognitive impairment, and low hand grip strength were significantly associated with 1-year mortality. Survival tree analysis showed that patients with BADL disability and high ACB carried the highest risk of poor survival [hazard ratio (HR): 16.48 (2.63-74.72)], followed by patients with BADL disability and low ACB (HR: 8.43, 95%CI:1.85-38.87). Patients with cognitive impairment and no BADL disability were characterized by a lower but still significant risk of mortality (HR:6.61, 95%CI:1.51-28.97) as well as those with high ACB score and good cognitive and functional performance (HR:5.28, 95%CI:1.13-24.55). Conclusions. BADL dependency, cognitive impairment and ACB score were the 3 main predictors of 1-year mortality among patients discharged from acute care hospitals; the interaction between BADL dependency and ACB score was found to significantly affect survival. Early identification of such high-risk patients may help tailoring targeted interventions to counteract their detrimental effects on prognosis.